Developing a Framework on Performance and Challenges of Strategic Management Information System: A Case study on Ministry of Interior, UAE - Hock, Oo Yu; Yaser Alraei, Alnekhaira Buti Alshamsi; Asif, Mahbub Karim; Mohammad Imtiaz, Hossain (2019)
This paper focuses on understanding the concept of information system (IS), information technology (IT), Strategic management information system (SMIS), the need for SMIS, the challenges of SMIS in implementation and the relevant models. Thus, this study proposes an integrated framework for the Performance and Challenges of Strategic Management Information System in the Ministry of interior, UAE. Undoubtedly, organizations are largely depending on information system now a days due to the advancement of information technologies. Public organizations should adopt their strategies to achieve their missions, but in the long run they face a myriad of challenges that threaten the fulfilment of this mission or the implementation of successful strategies in accordance with this mission. UAE also moving forward towards vision 2021. Implementing information technology strategically is very crucial for achieving these goals. Based on the literature, having a strategic planning system in place is not a guarantee that an organization will achieve its strategic goals and objectives. It is important to evaluate the strategic planning process involved and how it is linked to other management processes in an organization. This paper uses secondary data sources to analyse the existing literature and for deep understanding of concepts, trends and models. The expected results of the study will be helpful for the practitioners, academia, researchers, government officials and regulators.